Delay in primordial germ cell migration in adamts9 knockout zebrafish - Carver, Jonathan J. (Sci Rep, 2021)
Adamts9 (a disintegrin and metalloproteinase with a thrombospondin type 1 motif, member 9) is one of a few metalloproteinases structurally conserved from C. elegans to humans and is indispensable in germ cell migration in invertebrates. However, adamts9′s roles in germ cell migration in vertebrates has not been examined. In the present study, we found zygotic expression of adamts9 started around the germ ring stage and reached peak levels at 3 days post fertilization (dpf) in zebrafish. The migration of primordial germ cells (PGC) was completed within 24 hours (h) in wildtype siblings, while a delay in PGC migration was found at 15 and 24-h post-fertilization (hpf) in the Adamts9 knockout (KO). However, the delayed PGC migration in Adamts9 KO disappeared at 48 hpf. Our study suggests a conserved function of Adamts9 in germ cell migration among invertebrates and vertebrates. In addition, our results also suggest that Adamts9 is not essential for germ cell migration as reported in C. elegans, possibly due to expansion of Adamts family members and compensatory roles from other metalloproteinases in vertebrates. Further studies are required in order to elucidate the functions and mechanisms of metalloproteinases in germ cell migration and gonad formation in vertebrates.